Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Return on Assets Pada PT Waskita Karya Tbk Periode 2014-2023 - Bulan Oktrima; Hanny Alfiyyah Rahmawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study is motivated by fluctuations in the financial performance of construction companies, particularly PT Waskita Karya Tbk, which are closely related to liquidity management and capital structure decisions. In recent years, changes in short-term solvency and increasing reliance on debt have raised concerns regarding their impact on profitability. Therefore, this research aims to analyze the effect of the Current Ratio and Debt to Equity Ratio on Return on Assets, both partially and simultaneously, at PT Waskita Karya Tbk during the period from 2014 to 2023. The study adopts a quantitative method with an associative approach and utilizes secondary data obtained from the company’s annual financial statements over ten years. Data were analyzed using SPSS version 25 through classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and the coefficient of determination. The results indicate that the Current Ratio does not have a significant effect on Return on Assets, suggesting that high liquidity does not necessarily reflect efficient asset utilization. In contrast, the Debt to Equity Ratio has a significant negative effect on Return on Assets, indicating that excessive debt financing can reduce profitability. Simultaneously, both variables significantly influence Return on Assets, implying that liquidity and capital structure jointly play an important role in determining financial performance. These findings emphasize the need for balanced financial management to improve corporate profitability.